Sino-Swiss Free Trade Agreement - 2018 Academic Evaluation Report 中国-瑞士自由贸易协定 ‒ 2018 评估报告 - Casas, Tomas; Han, Jian; Legge, Stefan; Lu, Yue; Ziltener, Patrick; Tu, Xinquan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The first and immediate benefit of the SSFTA are practical opportunities resulting from exporters saving customs duties because of the substantial reductions in tariffs. The FTA created an annual savings potential for Swiss exporting firms worth several hundred million CHF (Ziltener, 2014), and well over 100 million were realized in 2017, on both the Chinese and Swiss sides. These significant amounts are expected to increase in the year 2018 and beyond